DiversifikasiI Pendapatan, Kinerja, dan Risiko pada Bank Syariah Indonesia Periode 2009-2018 - Mesta Pramika (Islamic Economics Study Program, Faculty of Sharia and Islamic Economics, Universitas Annuqayah, 2022)
This study aims to examine the effect of income diversification (DIVPEN) on the performance of banks using return on assets (ROA) proxies and liquidity risk using non-performing financing (NPF) proxies at Indonesian Islamic Banks. Observations were made on all Indonesian Islamic Banks, both in the form of Sharia Commercial Banks and Sharia Business Units registered with the Financial Services Authority during the 2009-2018 period. The analysis method uses multiple linear regression analysis. The results showed that DIVPEN had a significant positive effect on ROA and a negative effect on NPF.